Front Cover: Cover Image, Volume 21, Issue 4. Issue 4 (23rd July 2022) - Cheng, Zihang; Qiao, Dongling; Zhao, Siming; Zhang, Binjia; Lin, Qinlu; Xie, Fengwei
Abstract : The cover image is based on the Review Article Whole grain rice: Updated understanding of starch digestibility and the regulation of glucose and lipid metabolism by Dongling Qiao et al., https://doi.org/10.1111/1541-4337.12985 .